Contribution to the study of the arteries and veins of the renal hilum in Hereford bovines - Teixeira Filho, Althen; Fernandes Filho, Antonio; Miglino, Maria Angélica (Brazilian Journal of Veterinary Research and Animal Science, 1996)
Number and distribution of the arteries and veins of the renal hilum in bovines of Hereford breed were studied, after fixation in 10% formaldehyde solution. The arterial branches in the right kidney varied from 3 to 15 and in the left from 3 to 13. The venous roots varied from 4 to 12 in the right kidney and from 3 to 9 in the left. All these vessels were peripherally located.